Are complications after repairing acute Achilles tendon ruptures related to the surgical approach or the patient’s comorbidities?* - Parise, Ana Cecilia; Molho, Nicolás Martin; Naiman, Melanie; Valenti, Pablo; Cafruni, Virginia María; Villena, Daniel Sebastián; Bilbao, Facundo; Santini Araujo, María Gala; Conti, Leonardo Angel; Cardone, Guillermo; Sotelano, Pablo; Carrasco, Marina (Journal of the Foot & Ankle, 2023)
Objective: Analyze the postoperative complications after repairing acute Achilles tendon rupture and compare them according to the surgical approach (open surgery (OS) or minimally invasive surgery (MIS)) and the patient’s comorbidities. Methods: A retrospective analytical study including 154 consecutive patients with an acute Achilles tendon rupture submitted to surgery and divided into OS and MIS cohorts. The following relevant comorbidities were analyzed: obesity, diabetes mellitus, smoking, dyslipidemia, gout, chronic corticosteroid use, connective tissue pathologies, transplant history, cancer treatment patients, and postoperative complications. Results: Seventy-eight patients (50.6%) were treated surgically with an OS technique and 76 (49.4%) with an MIS approach. Twenty patients (13%) had postoperative complications between the two cohorts (OS 11.5%; MIS 14.5%; p = 0.588). No statistically significant difference was found in the logistic regression of the risk of the surgical approaches and complications. Obesity had a significant statistical difference when complications and comorbidities were compared. Conclusions: Patients with obesity have a higher risk of developing postoperative complications with both OS and MIS techniques. No relationship was found between the type of surgical approach and a higher percentage of postoperative complications in treating acute Achilles tendon rupture.